Recontextualizing Modernity: A Case Study of The Kaum Adat in Padangpanjang Through the Boedi-Tjaniago (1920s) - Oktaviani, Saktia; Andoni, Yudhi (Jurnal Ceteris Paribus, 2024)
In this study, the newspaper Boedi Tjaniago (1922) is examined to gain insight into how ideas of progress and modernization were represented in Minangkabau in the early 1900s. The historical method, inclusive of heuristic, criticism, interpretation and historiography stages, was employed for analysis. The primary data source was the newspaper Boedi Tjaniago from PDIKM Padangpnjang. The findings of this research reveal that Boedi Tjaniago was a significant media outlet that embodied the modernization movement in Minangkabau during the early 1900s. In addition to disseminating progressive concepts, this newspaper also played a role in forging the identity and cohesiveness of the Minangkabau people. Keywords: Boedi Tjaniago, newspapers, modernization, Minangkabau, progress